2012
DOI: 10.1002/jctb.3902
|View full text |Cite
|
Sign up to set email alerts
|

Box–Behnken factorial design study of the variables affecting metal electrodeposition in membraneless fluidized bed electrodes

Abstract: BACKGROUND: Heavy metal removal from industrial wastewaters has been studied intensively since it is well known that they can cause severe problems to human health and aquatic life, even at very low concentrations. Traditional precipitation or adsorption technologies only transfer the problem to the solid phase, therefore new technologies, such as electrodeposition using fluidized bed electrodes (FBE), have been considered to avoid contamination. RESULTS: Copper electrodeposition from diluted solutions was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…3a that the operational conditions (I and E) and C s had main influence on the value of CE act , while C 0 influenced ACE since the initial concentration determines the relative contribution of the activated control and the mass transfer control to the overall reaction. The role of I, E, and C s on CE act was already studied in a previous work (Tonini et al 2013), but in order to optimize the process as Heavy metal removal from simulated wastewater… a whole, in this study the influence of mass transfer and C 0 on the average process responses were also considered. The values of IEC were inversely proportional to ICE [Eq.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3a that the operational conditions (I and E) and C s had main influence on the value of CE act , while C 0 influenced ACE since the initial concentration determines the relative contribution of the activated control and the mass transfer control to the overall reaction. The role of I, E, and C s on CE act was already studied in a previous work (Tonini et al 2013), but in order to optimize the process as Heavy metal removal from simulated wastewater… a whole, in this study the influence of mass transfer and C 0 on the average process responses were also considered. The values of IEC were inversely proportional to ICE [Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The variables affecting cadmium removal using a rectangular spouted bed reactor were described by Baghban et al (2014). Although there have been several reports concerning the use of fixed bed electrodes, studies of fluidized bed reactors are lacking (with the exception of our own work, reported by Tonini et al 2013). The most recent article concerning the use of a FBE for metal recovery was published by Thilakavathi et al (2012), who used a theoretical model to predict the bed thickness and hydrodynamic behavior of the conducting particles in an expanded bed reactor.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations